Effect of two surfactants on in vitro permeation of butorphanol through horse nasal mucosa - Velloso, María Inés (2021)
The aim of the present study was to evaluate the effect of two surfactants on in vitro permeation of butorphanol through equine nasal mucosa. Franz diffusion cells and equine nasal mucosa were used. Three formulations were developed based on citric acid, sodium citrate, sodium chloride, and butorphanol tartrate and administered at a 24.4 g cm-3 dose. Control formulation lacked any penetration enhancer. Formulation 1 (F1) had a cationic surfactant (cetrimonium bromide) and formulation 2 (F2) had a non-ionic surfactant (Tween 80). Statistically comparing flux values at the steady state (Jss), apparent permeability coefficient (Kp), and lag-time from control, F1 and F2 for the respiratory region does not show statistically significant differences (α= 0.05). However, statistically significant differences were found on the Jss and Kp, values from control, F1, and F2 in olfactory mucosa. A statistical analysis on the latter showed significant differences between the Jss values of F1 and F2 and between control and F2. Based on this, Tween 80 proved to be a promising excipient in developing intranasal butorphanol formulations in equines since it increases its passage through the nasal mucosa. These results are very promising to continue with the development of intranasal butorphanol formulation in equines.